Corporate Social Responsibility Program Implementation of PT. Tunggal Perkasa Plantation in Indragiri Hulu District - Made Devi Wedayanti; Boby Indra Pulungan; Moris Adidi Yogia; Panca Setyo Prihatin (SOSHUM : Jurnal Sosial dan Humaniora, 2022)
Tunggal Perkasa has four CSR programs but one program is not running, namely the program in the field of Economics (Community Empowerment and Training Center). The research objective was to determine the implementation of PT.Tunggal Perkasa Plantation's CSR program in the economic field. Employing qualitative methods, the data were collected using interview techniques, observation, and the latest documentation. The findings of this study are that the implementation of CSR in the economic field provided by PT Tunggal Perkasa Plantation in the community has mostly not been realized according to the target. The novelty of this research is that the implementation of CSR programs needs to be supported by transparency and government intervention in providing CSR funds to the community.